Functionalization of Semi-conductive Interfaces with Cucurbit[n]urils - Ngwekazi, Andisiwe; Arendse, Christopher; Baker, Priscilla (Mini-Reviews in Organic Chemistry, 2025)
Cucurbiturils are a class of macrocyclic compounds with highly polar carbonyl portals and a hydrophobic cavity. They are usually utilized as efficient host molecules in supramolecular chemistry applications due to their high binding affinity for positively charged or cationic compounds. This review investigates the application of CB[n] immobilization at semi-conductive interfaces to produce electrochemical sensors. Critical to the production of thin film electrode preparations is the solubility of the CB[n] to produce homogeneous thin films when deposited. The solubility of CB[n] molecules in organic and inorganic solvents is limited; however, CB[7] has been applied successfully in the production of a wide range of electrochemical sensors. Furthermore, we introduce simple drop-casting of efficiently solubilized CB[7] as a simple yet effective method for producing CB[7] modified electrochemical sensors for the sensitive reporting of dopamine in aqueous solutions in the concentration range of 3.33×10-9 to 1.16×10-8 M with a sensitivity of 0.315 µA/M, (n=3).
Keywords: homogeneous thin films